Eicosapentaenoic acid-enriched phospholipids improve Aβ1–40-induced cognitive deficiency in a rat model of Alzheimer's disease. (June 2016) - Wen, Min; Xu, Jie; Ding, Lin; Zhang, Lingyu; Du, Lei; Wang, Jingfeng; Wang, Yuming; Xue, Changhu
Highlights: This is the first study to demonstrate the protective effect of EPA-PL on Aβ-induced cognitive deficiency in AD model rats. EPA-PL improved Aβ-induced brain dysfunction uncoupled with brain DHA increase. The mechanism of EPA-PL involved in ameliorating Aβ-induced oxidative stress, inflammation and hyper-phosphorylated Tau. Abstract: Abundant studies have proven that the protective effects of omega-3 polyunsaturated fatty acids enriched phospholipids (n-3 PUFA-PLs) mainly derived from fish roe and Antarctic krill have beneficial effects on cognition. However, the n-3 PUFA-PLs are usually a mixture of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) enriched phospholipids. Hence, the effects of EPA-PLs alone on cognitive deficiency are still unclear. In the present study, we obtained almost pure EPA-PLs (EPA:DHA = 47.9:2.08) from the sea cucumber, Cucumaria frondosa, and investigated its effects on Aβ-induced cognitive impairment in rats. Administration of EPA-PLs (150 and 300 mg/kg⋅day, i.g., 27 days) did not increase brain DHA but significantly improved Aβ-induced cognitive deficiency. Further mechanism research indicated that EPA-PLs alleviated Aβ-induced neurotoxicity including oxidative stress, apoptosis, neuro-inflammation cascade, and hyper-phosphorylated tau in a dose-dependent pattern. These findings first suggest that EPA-PLs could also improve Aβ induced cognitive deficiency in a similar mechanism with DHA-PLs.